Measuring Structural Deformations in the Laboratory Environment Using Smartphones - Kromanis, Rolands; Xu, Yan; Lydon, Darragh; Martinez del Rincon, Jesus; Al-Habaibeh, Amin (Frontiers in Built Environment, 2019)
The engineering education and research sectors are interlinked, and there exists a need within both for readily deployable low-cost systems. Smartphones are affordable and easy to use technology available to almost everyone. Images or video frames taken with smartphone cameras, of structures subjected to loadings, can be analysed to measure structural deformations. Such applications are very useful for university students and researchers when performing tests in laboratory environments. This paper investigates the feasibility of using smartphone technologies to measure structural deformation in the laboratory environment. Images and videos collected while structures are subjected to static, dynamic and quasi-static loadings are analysed with freeware and proprietary software. This study demonstrates capabilities of smartphone technologies, when coupled with suitable image processing software, for providing accurate information about structural deformations. Smartphones and open source software are affordable and available in comparison to professional cameras and proprietary software. The technology can be further developed to be used in real world environments to monitor deformation of engineering structures.